2014
DOI: 10.1007/s40737-014-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the Sense of Self in the Process of Recovery in Schizophrenia

Abstract: Recovery oriented services extend beyond reduction of psychiatric symptoms and focus on helping individuals reconstruct their lives in a meaningful way. This case report describes the rehabilitation interventions with a 37 year old woman with chronic schizophrenia and residual disability during a four-month inpatient stay. These comprised individual supportive psychotherapy with vocational rehabilitation, social skills training and behavioural management components. Family intervention addressed maternal criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Discrimination has been shown to promote the adoption of a paranoid external attributional style (Janssen et al, 2003), which could eventually predispose the individual to PS/PEs (Bentall, Kinderman, & Kaney, 1994; Kinderman & Bentall, 1996; Sharpley, Hutchinson, Murray, & McKenzie, 2001) by promoting the development of ‘high aberrant salience’ (Kapur, 2003). Discriminatory treatment could also foster a sense of social failure and more particularly low self-esteem (Crocker & Major, 1989; Saleem et al, 2014) and thus lead to a low self-concept clarity (Campbell, 1990), which is in part due to internalized stigma (Mathur, Bhola, Khanam, & Thirthalli, 2014). These specific disturbances in social cognition may lead to the development of PS/PEs (Moller & Husby, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination has been shown to promote the adoption of a paranoid external attributional style (Janssen et al, 2003), which could eventually predispose the individual to PS/PEs (Bentall, Kinderman, & Kaney, 1994; Kinderman & Bentall, 1996; Sharpley, Hutchinson, Murray, & McKenzie, 2001) by promoting the development of ‘high aberrant salience’ (Kapur, 2003). Discriminatory treatment could also foster a sense of social failure and more particularly low self-esteem (Crocker & Major, 1989; Saleem et al, 2014) and thus lead to a low self-concept clarity (Campbell, 1990), which is in part due to internalized stigma (Mathur, Bhola, Khanam, & Thirthalli, 2014). These specific disturbances in social cognition may lead to the development of PS/PEs (Moller & Husby, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…2,9 Recovery can include experiences that are difficult to quantify or observe by others, because as fundamentally subjective matters they can only be known by the recovering person. [10][11][12] This growing work on recovery has pointed to the need to revisit the purposes and mechanisms of mental health treatment. If deeply subjective change is at issue, then teaching skills and reducing symptoms may not go far enough in promoting recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies sheds light on how conflicting feelings about ethnicity and perceived ethnic discrimination are associated with poorer psychosocial, academic and health outcomes (Knauss et al , 2015; Rivas-Drake et al , 2014). Consequently, societal stigma and culture on how the person makes sense of these difficulties, the effects of experiences with services, and loss of employment and other social roles that act is important to identity have a further impact on poor mental health (Mathur et al , 2014). We have observed that the process of reconnection and reconciliation with the person’s own cultural roots was an important part of their recovery journey, in particular for those who did not feel Trieste was their chosen living community.…”
Section: Discussionmentioning
confidence: 99%